(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Fast-track anaesthesia which includes early extubation after cardiac surgery is frequently done as a way to facilitate speedy recovery and early discharge from intensive care unit (ICU), thereby, reducing costs and avoiding other complications Method: The study was designed as a 6 month retrospective study with two groups. Hundred patients undergoing elective off pump coronary bypass grafting(CABG) were divided into two groups . The first fastrack group following the new early extubation protocol, while the other group was extubated according to the old conventional extubation protocol after CABG. The arterial blood gas(ABG) analysis were performed at two different interval post extubation (20 minutes and 4 hours) to compare the effect of new fastrack extubation protocol on the ABG parameters. Results: At both 20 minutes and 4 hours interval, the partial pressure of oxygen, PaO2 / FiO2 ratio in the fast track group was better as compared to the patients undergoing extubation via conventional method. PCO2 four hours post-extubation were lower in the fast track group and the results were statistically significant. Conclusion: The early extubation protocol improved respiratory parameters like oxygenation profile as well as lower pco2 levels post extubation.